Coping Styles in Twins Discordant for Schizophrenia, Bipolar Disorder, and Depression. (March 2016) - Fortgang, Rebecca G.; Hultman, Christina M.; Cannon, Tyrone D.
Schizophrenia, bipolar disorder, and major depression share several clinical and etiological factors. Coping is a critical mediator of the relationship between stress and psychopathology and a point of clinical intervention for all three disorders; however, little is known about their degree of overlap in coping style or the influence of unique or shared genetic diathesis. In this study, we examined five factors of coping within and across disorder proband and co-twin groups, modeled heritability, and tested for endophenotypic pattern in a sample of twin pairs recruited from the Swedish Twin Registry ( N = 420). Although there was substantial phenotypic overlap across disorders, including low levels of productive problem-focused coping and high levels of disengagement, each disorder was associated with a unique profile across other dimensions of coping. We also found evidence of heritability for three of five factors, yet we found little evidence of genotypic overlap among disorders contributing to similar strategy use.